Dietary and Lifestyle Factors Related to Gastroesophageal Reflux Disease: A Systematic Review - Zhang, Mei; Hou, Zheng-Kun; Huang, Zhi-Bang; Chen, Xin-Lin; Liu, Feng-Bin (Therapeutics and clinical risk management, 2021)
We performed this review to clarify which dietary and lifestyle factors are related to gastroesophageal reflux disease. Through a systematic search of the PubMed, EMBASE, China National Knowledge Infrastructure (CNKI), and Chinese BioMedical Literature (CBM) databases, we identified articles with clear definitions of GERD, including nonerosive gastroesophageal reflux disease (NERD), reflux esophagitis (RE) and Barrett's esophagus (BE), that included dietary and lifestyle factors as independent factors affecting the onset of GERD (expressed as odds ratios (ORs) or relative risks (RRs) and 95% confidence intervals (CIs)). Due to heterogeneity among the studies, we used descriptive statistical analyses to analyze and synthesize each outcome based on the disease type. In total, 72 articles were included, conducted in ten Western countries (26 articles in total) and nine Eastern countries (46 articles in total). We categorized dietary factors into 20 items and lifestyle factors into 11 items. GERD is related to many irregular dietary and lifestyle habits (such as a habit of midnight snacking: OR=5.08, 95% CI 4.03-6.4; skipping breakfast: OR=2.7, 95% CI 2.17-3.35; eating quickly: OR=4.06, 95% CI 3.11-5.29; eating very hot foods: OR=1.81, 95% CI 1.37-2.4; and eating beyond fullness: OR=2.85, 95% CI 2.18-3.73). Vegetarian diets (consumption of nonvegetarian food (no/yes); OR=0.34, 95% CI 0.211-0.545) and no intake of meat (OR=0.841, 95% CI 0.715-0.990) were negatively related to GERD, while meat (daily meat, fish, and egg intake: OR=1.088, 95% CI 1.042-1.135) and fat (high-fat diet: OR=7.568, 95% CI 4.557-8.908) consumption were positively related to GERD. An interval of less than three hours between dinner and bedtime (OR=7.45, 95% CI 3.38-16.4) was positively related to GERD, and proper physical exercise (physical exercise >30 minutes (>3 times/week): OR=0.7, 95% CI 0.6-0.9) was negatively correlated with GERD. Smoking (OR=1.19, 95% CI 1.12-1.264), alcohol consumption (OR=1.278, 95% CI 1.207-1.353) and mental state (poor mental state: OR=1.278, 95% CI 1.207-1.353) were positively correlated with GERD. RE (vitamin C: OR=0.46, 95% CI=0.24-0.90) and BE (vitamin C: OR=0.44,95% CI 0.2-0.98; vitamin E: OR=0.46, 95% CI 0.26-0.83) were generally negatively correlated with antioxidant intake. In conclusion, many dietary and lifestyle factors affect the onset of GERD, and these factors differ among regions and disease types. These findings need to be further confirmed in subsequent studies.